1999
DOI: 10.1007/3-540-48873-1_25
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Tabu Search Algorithm for the Nurse Rostering Problem

Abstract: Abstract. This paper deals with the problem of nurse rostering in Belgian hospitals. This is a highly constrained real world problem that was (until the results of this research were applied) tackled manually. The problem basically concerns the assignment of duties to a set of people with different qualifications, work regulations and preferences. Constraint programming and linear programming techniques can produce feasible solutions for this problem. However, the reality in Belgian hospitals forced us to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
121
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 6 publications
1
121
0
2
Order By: Relevance
“…In order for the choice function based hyperheuristics to initialise the values of f 1 , f 2 , f 3 , and F for each neighbourhood, we randomly call the neighbourhoods for an initial warm-up period. This warm-up period is included in the time allowed to the choice function based hyperheuristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order for the choice function based hyperheuristics to initialise the values of f 1 , f 2 , f 3 , and F for each neighbourhood, we randomly call the neighbourhoods for an initial warm-up period. This warm-up period is included in the time allowed to the choice function based hyperheuristics.…”
Section: Resultsmentioning
confidence: 99%
“…The small term ε/10η should enable every neighbourhood, no matter how bad, to be able to come around and diversify the solution after every other neighbourhood has been visited about 10 times. The fourth DECOMPCHOICE method considers the individual components f 1 , f 2 and f 3 , of F. It tries the (up to four) low level heuristics which yield the best values of f 1 , f 2 , f 3 , and F and performs the best move yielded by one of these low level heuristics..…”
Section: The Choice Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some earliest techniques utilized for the NRP include integer programming [4], [5], goal programming [6], case-based reasoning [7], [8] and constraint Programming [9], [10]. In the recent time, some of the metaheuristic techniques that have also been employed for the NRP are local search-based approaches, which include tabu search [11], [12], simulated annealing [13], variable neighbourhood structures (VNS) [14], [15]. Others are population-based approaches like ant colony optimization [16], genetic algorithm (GA) [17], [18], harmony search algorithm (HSA) [19], [20], particle swarm optimization [21].…”
Section: Introductionmentioning
confidence: 99%
“…Variations in research are observed in the areas of application and in the definition of the problem, as well as in the employed solution methods: Jaumard (Jaumard et al, 1998), Chun (Chun et al, 2000), Barboza (Barboza et al, 2003), Meisels and Schaerf (2003), and Özcan (2005). Currently, in the literature one can find real cases of the rostering problem treated with metaheuristics: Simulated Annealing as in Dowling (Dowling et al, 1997), Tabu Search (TS) as in Dowsland (Dowsland, 1998) and Burke (Burke et al, 1998), Genetic Algorithms (GA) as in Burke (Burke et al, 2001), Özcan (Özcan, 2005), Yeh (2007) and Tsai (Tsai and Li, 2009), and Iterated Local Search. Due to the large number of variables and constraints involved, it is classified as a NP-Hard optimization problem (Burke et al, 2003;Osogami and Imai, 2000).…”
Section: Introductionmentioning
confidence: 99%